(untitled) (International Journal of Engineering and Computer Science, 2019)
Online Analytical Processing (OLAP) is playing a vital role in today’s business work as well as in other domain. It gives the users an analytical view of data resulting in effective decision making. Many domains are applying Online Analytical Processing (OLAP) for different kinds of analysis due to its excellent performance and wide adaptability, such as analysis of network traffic and remote sensing images. The objective of this work therefore is to develop a web result portal that will enable lecturers post and compare students’ results for quick assessment. I was motivated in order to reduce stress, workload and discomfort always encountered by the lecturers and school examination body during computation, compilation and reconciliation of students’ results. Object-Oriented Analysis (OOADM) will be adopted as the methodology while Java will be used as the programming language. The expected result is web-based software for students result processing that will eliminate the problems of manual database system used in tertiary institutions.